2013
DOI: 10.1136/bmjopen-2013-003217
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to, and facilitators in, introducing integrated diabetes care in Ireland: a qualitative study of views in general practice

Abstract: ObjectiveTo examine the barriers to, and facilitators in, improving diabetes management from the general practice perspective, in advance of the implementation of an integrated model of care in Ireland.DesignQualitative using semistructured interviews.SettingPrimary care in the Republic of Ireland.ParticipantsPurposive sample of 29 general practitioners (GPs) and two practice nurses.MethodsData were analysed using a framework approach.ResultsThe main barriers and facilitators occurred at the level of the healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 31 publications
(31 reference statements)
2
53
0
Order By: Relevance
“…The topic guide focused on five key issues: how diabetes care was delivered in the practice; challenges to managing diabetes effectively and efficiently; ‘wish list’ for diabetes care in Ireland; changes in care provision at local and national level; and attitudes to the development of national diabetes register. This paper focuses on the themes which emerged in relation to the last two topics; the results of discussions on the other topics are published elsewhere 8. Prompts included the advantages of a regionally versus nationally coordinated register, desirable content and format including key indicators, necessary conditions for implementation and barriers to change.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The topic guide focused on five key issues: how diabetes care was delivered in the practice; challenges to managing diabetes effectively and efficiently; ‘wish list’ for diabetes care in Ireland; changes in care provision at local and national level; and attitudes to the development of national diabetes register. This paper focuses on the themes which emerged in relation to the last two topics; the results of discussions on the other topics are published elsewhere 8. Prompts included the advantages of a regionally versus nationally coordinated register, desirable content and format including key indicators, necessary conditions for implementation and barriers to change.…”
Section: Methodsmentioning
confidence: 99%
“…Little is known about engagement in quality improvement within the Irish health system as initiatives are often ‘sporadic and individually driven’ 7. Efforts to improve the quality of diabetes care in particular are frequently confined to pockets of interested individuals 8. Qualitative research allows us to explore attitudes while also identifying the beliefs, perceptions and social norms that shape them 9.…”
Section: Introductionmentioning
confidence: 99%
“…A study confirmed that the main barriers at health care system level including, lack remuneration for diabetes management, lack coordination between setting and deficiency access the services. This lack of remuneration could lead to stunt in practice development and low a sense of apathy among healthcare providers (54) Other issues in the healthcare system level related to the integration between setting and professionals as a resource. This condition leads to a sense of ambiguity around the patients' care pathway and waiting times for the patients in the healthcare services (54).…”
Section: Health Systemmentioning
confidence: 99%
“…Only a few research reports assessed integrated care from the perspective of healthcare professionals [14][15][16]. Stephenson et al, performed a rapid review of all quantitative surveys and qualitative research studies to assess healthcare professionals' experiences with integrated care [14].…”
mentioning
confidence: 99%